Peak-to-average power ratio reduction in optical-OFDM systems using lexicographical permutations - Niwareeba, Roland (University of the Witwatersrand, Johannesburg, 2023)
The work presented in this thesis extends and contributes to the research in reducing the high Peak-to-Average Power Ratio (PAPR) in optical-Orthogonal Frequency Division Multiplexing (OFDM) systems using probabilistic-based and hybrid techniques. Whereas the high PAPR problem has been extensively studied and a number of solutions provided for the conventional Radio Frequency (RF)-OFDM systems, there are only a few solutions proposed specifically for PAPR reduction in optical-OFDM systems. Although the probabilistic-based techniques such as Conventional Selected Mapping (CSLM) and Data Position Permutation (DPP) result into significant PAPR reduction performance with negligible Bit Error Rate (BER) degradation, the resulting increase in both hardware and computational complexity as a result of a large number of Inverse Fast Fourier Transform (IFFT) operations that have to be performed to generate the candidate signals is still a major drawback. In order to reduce the complexity, in this research, two techniques which are applied in opticalOFDM systems are proposed. The first technique is the hybrid method composed of a modified CSLM and µ-law companding techniques called Low Complexity Hybrid Selected Mapping (LCHSLM). The proposed method achieves almost 50% reduction in complexity compared to CSLM with less BER degradation. The second technique based on lexicographical permutations called Lexicographical Symbol Position Permutation (LSPP) works by dividing the optical-OFDM symbol into a number of sub-blocks and performing lexicographical permutations to obtain the candidate signals after the IFFT operations. In the proposed LSPP, all the candidate permutation sequences are not obtained at once unlike in the DPP where the number of candidate permutation sequences increases at a factorial rate of growth as the number of sub-blocks increases resulting in a more complex system. Additionally, the research proposes an algorithm where a threshold PAPR value is introduced and the candidate signals are generated until a candidate with a PAPR value less or equal to the threshold is obtained. The results show that the complexity in terms of IFFT operations can be reduced substantially depending on the selected threshold and the number of candidate signals. Furthermore, the research introduces a new algorithm based on the global gain (net gain) to determine the most suitable number of permutation candidate sequences to achieve a reasonable PAPR reduction performance without increasing the time and hardware complexity to levels that the systems cannot tolerate.
A thesis submitted in partial fulfilment of the requirements for the degree Doctor of Philosophy to the Faculty of Engineering and the Built Environment, School of Electrical and Information Engineering, University of the Witwatersrand, Johannesburg, 2023
Keywords: Peak-to-Average Power Ratio (PAPR); Orthogonal Frequency Division Multiplexing (OFDM); Conventional Selected Mapping (CSLM); Data Position Permutation (DPP); Lexicographical Symbol Position Permutation (LSPP); Inverse Fast Fourier Transform (IFFT); Bit Error Rate (BER); UCTD